2020
DOI: 10.1111/josh.12868
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Health Education Course on Pre‐Service Teachers' Perceived Knowledge, Skills, Preparedness, and Beliefs in Teaching Health Education

Abstract: BACKGROUND:In this study, we explore how a health education course may play a role in pre-service teachers' perceptions in teaching and integrating health education activities to nurture K-8 students' health literacy. METHODS:We used mixed methods to examine the effect of a health education course in a teacher education program. Of 55 pre-service teachers, 41voluntarily participated in the study. Quantitative data were obtained through an online questionnaire administered to participants at the beginning and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
0
8
0
3
Order By: Relevance
“…El equipo investigador podría ocuparse de la formación, evaluación y asesoramiento en dichos programas escolares. En estas sesiones formativas se podrían trabajar aspectos como la sensibilización, los modelos de promoción de salud, el conocimiento sobre diferentes comportamientos saludables, así como diferentes estrategias efectivas (Vamos, Xie, & Yeung, 2020). Asimismo, podría ser interesante dotar al profesorado de recursos y herramientas didácticas como guías de promoción de hábitos saludables, libros, blogs, presentaciones, vídeos didácticos con las sesiones implementadas en otros centros educativos o materiales para poder utilizar.…”
Section: De La Reflexión a La Práctica: Consideraciones Metodológicasunclassified
“…El equipo investigador podría ocuparse de la formación, evaluación y asesoramiento en dichos programas escolares. En estas sesiones formativas se podrían trabajar aspectos como la sensibilización, los modelos de promoción de salud, el conocimiento sobre diferentes comportamientos saludables, así como diferentes estrategias efectivas (Vamos, Xie, & Yeung, 2020). Asimismo, podría ser interesante dotar al profesorado de recursos y herramientas didácticas como guías de promoción de hábitos saludables, libros, blogs, presentaciones, vídeos didácticos con las sesiones implementadas en otros centros educativos o materiales para poder utilizar.…”
Section: De La Reflexión a La Práctica: Consideraciones Metodológicasunclassified
“…The literature review presents limited health education study, focused on training trained teachers and to apply specific health programs for primary school students (Pickett, Shepherd, Roderick & Grace, 2017;Vamos, Xie & Yeung, 2020). A targeted search revealed the lack of studies focused on the health education of the education student during his undergraduation, with the intention of promoting a personal experience that encourages him to establish a healthy lifestyle.…”
Section: Introductionmentioning
confidence: 99%
“…A targeted search revealed the lack of studies focused on the health education of the education student during his undergraduation, with the intention of promoting a personal experience that encourages him to establish a healthy lifestyle. However, there is agreement that there is a need for university health literacy programs for future teachers (Vamos et al, 2020), since the undergraduate stage comprises a propitious stage to expand knowledge and experience transformative experiences, which will increase their training (Sarcona et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, previous research suggests that current teacher training approaches to preparing teachers to teach health are not adequate (Speller et al, 2010). Indeed, there are many teachers who consider themselves unprepared to effectively teach a health curriculum (Vamos et al, 2020). In has long been viewed that adequate teacher preparation presents as a considerable obstacle to developing student health literacy (Peterson, Cooper, & Laird, 2001).…”
mentioning
confidence: 99%
“…To be sure, Carr, Wei, Kutcher, and Heffernan (2018) reported that even a one-day workshop, focused on basic concepts about mental health and mental illness, can improve pre-service teachers' mental health literacy. In an intervention study undertaken at Western Michigan University, pre-service teachers participated in a health education course designed to promote health literacy (Vamos et al, 2020). At the conclusion of the course, the participants reported that they were more prepared to teach health and integrate learning in health literacy into their teaching.…”
mentioning
confidence: 99%